Wireless Crime and Forensic Investigation - Kipper, Gregory (CRC Press, 2009)
Security is always a concern with any new technology. When we think security we typically think of stopping an attacker from breaking in or gaining access. However, based on the broad reach of wireless, stopping someone from passively listening is just as critical. Intrusion detection systems, firewalls, and forensics are just a few of the key areas that must be understood and applied to proactively solve the wireless problem.